STUDI KOMPARATIF PANDANGAN IMAM ABU HANIFAH DAN HUKUM PERDATA TERHADAP PEMBUNUHAN SEBAGAI PENGHALANG KEWARISAN - Nur Esa; Asni Zubair; Dr. Firdaus M.H (IAIN BONE, 2022)
AbstractThis article examines the comparison of Imam Abu Hanifah's views and Civil Law regarding murder as a barrier to receiving inheritance. The aim is to find out the views of Imam Abu Hanifah and the civil law regarding murder as a barrier to receiving inheritance, in terms of similarities and differences in their views. This research is normative with a qualitative approach, and is supported by secondary data sources from fiqh books and the Civil Code, which are then analyzed using qualitative descriptive to describe the research results.The results of the study show that: First, the opinion of Imam Abu Hanifah regarding murder is one of the barriers for someone to get an inheritance which clearly states the type of murderer, namely murder with qisas and/or kaffarah sanctions, namely intentional murder, intentional similar murder, murder by mistake and murder considered is wrong, while the civil law code also explains that murder can prevent heirs from receiving an inheritance, in article 838 paragraph 1. Second, the similarity between the two in the concept of determining murder as a barrier to receiving an inheritance is an additional punishment for those who commit murder. and the loss of the right of the heirs to inherit. Meanwhile, the difference lies in the type of murder, according to Imam Abu Hanifah, murder that causes a person to be prevented from receiving an inheritance, namely all murders with qisas and kaffarah sanctions, namely intentional killing, intentional similar killing, killing by mistake and murder is considered wrong, and according to civil law any type of murder can prevent a person from inheriting.Keywords: Abu Hanifah; Civil law; Inheritance Barrier; Murder.